Generational Gaps in Work-Life Balance: Comparing the Expectations of Gen X, Y, and Z - David Manafe; Maria Odriana Veronica Moi (Jurnal Dinamika Manajemen, 2025)
This study analyzes the relationship between work-life balance and employee happiness and performance, considering the differences between Generations X, Y, and Z in East Nusa Tenggara Province. This is an explanatory quantitative study with a sample size of 1.155 respondents and data analysis using SEM-PLS. Work-life balance is measured through three dimensions: Personal Life Interferes with Work (PLIW), Work Interferes with Personal Life (WIPL), and Work-Personal Life Enhancement (WPLE). The results indicate that among Generation Z, work-life balance significantly influences performance, with happiness as a mediator and moderator variable. Conversely, among Generation X and Y, the significant influence only occurs through the WPLE dimension, and happiness acts as a mediator without a moderating effect. These findings emphasize the importance of considering generational differences in human resource management strategies, particularly in designing flexible work systems that support employees’ responsibilities.